1975
DOI: 10.1113/expphysiol.1975.sp002297
|View full text |Cite
|
Sign up to set email alerts
|

The Oxygen Consumption, Fatty Acid and Glycerol Uptake of the Liver in Fed and Fasted Sheep During Cold Exposure

Abstract: The effect of a short period (3-4 hr) of exposure to cold on the liver's circulation and metabolism has been studied in sheep fed 6 hr or 21 hr before experiment.In the cold the animals had a significantly increased heart rate, cardiac output, hepatic portal blood flow, mean arterial blood pressure and pulse pressure. Total peripheral resistance fell in the fasted animals when they were exposed to cold, but not the more recently fed animals. Exposure to cold significantly increased the total body oxygen consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
13
1

Year Published

1977
1977
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 27 publications
11
13
1
Order By: Relevance
“…The significant increase in whole-body oxygen consumption in response to cold is consistent with previous observations reported in the literature (Thompson et al 1975;Webster et al 1969). These authors showed that cold exposure caused at least a two-fold increase in metabolic activity, a change comparable with the response observed in the present study.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The significant increase in whole-body oxygen consumption in response to cold is consistent with previous observations reported in the literature (Thompson et al 1975;Webster et al 1969). These authors showed that cold exposure caused at least a two-fold increase in metabolic activity, a change comparable with the response observed in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…The increase in whole body oxygen consumption in response to feeding is in agreement with published results (Webster and Hays 1968;Thompson et al 1975;Christopherson and Brockman 1989). The lack of response to the β-blockers only partially agrees with the data of Christopherson and Brockman (1989) For personal use only.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations